A high-efficiency automatic pressure-relief drug transfer device for anticancer medications with superior closed performance - Xie, Liming; Chen, Guanfeng; Ouyang, Qianqian; Quan, Weiyan; Xie, Xiaoming; Chen, Xiaoling; Li, Lefan; Li, Sidong; Chen, Rizhi; Luo, Rongqiong; Qiu, Zhiqing (Frontiers in Pharmacology, 2025)
ObjectivePreventing exposure to hazardous drugs is crucial for healthcare workers to avoid health risks. To mitigate healthcare workers’ risks when handling hazardous drugs, we developed a novel closed-system drug-transfer device (CSTD) called CSTD(JLY). This CSTD has an automatic pressure-relief structure. Hence, it can significantly decrease the resistance in the push/pull of a piston rod if an operator transfers drugs, thereby reducing the burden on the hands of the operator during drug transfer.MethodsWe investigated the closed performance of the novel CSTD (JLY) by comparing it with the performance of a syringe. We selected a simulation drug (fluorescein sodium), commonly used drugs (lansoprazole, nimodipine, and tropisetron), and a commonly used anti-cancer agent (cyclophosphamide) to conduct exposure evaluation.ResultsCompared with a syringe, CSTD(JLY) could reduce drug leakage significantly. Our novel CSTD with an automatic pressure-relief structure had superior closed performance. CSTD(JLY) could solve the problem of liquid-drug leakage during drug transfer.ConclusionThis feature could reduce the exposure risk healthcare workers and patients.